Handling Water Leaking on The Turbine Pit ULPLTA Bakaru due to Damage of the Guide Vane Part using Automatic Method with Motorized Valve - Ardhianto, Mochamad Marte; Sumarwanto, Rudi (INTEK: Jurnal Penelitian, 2021)
The Bakaru PLTA is the largest hydroelectric power plant in South Sulawesi with a capacity of 126 MW. To generate that much power, a lot of water is required, therefore, the Bakaru hydropower dam is designed to be able to accommodate a lot of water. In operation, the Bakaru hydropower plant consists of 2 units. However, not all units operate normally, such as unit 2. In unit 2, there is a leak that occurs in the Turbine Pit. This leak is caused by abrasion of the u-packing guide vane. With a leak in the turbine pit, more approaches are needed to dispose of the water in the turbine pit to the pit drainage. Which later developed into an infusion system that utilizes gravity to discharge water from the turbine pit in basement 2 to the drainage pit in basement 3. However, in its development, it turns out that the volume of water discharged cannot be controlled so that, it can cause a condition where one day the infusion hose does not flow and causes an increase in the water level in the turbine pit. This rise in the level of the turbine pit is dangerous for the unit. This is because water can enter the breathing hole of the bearing turbine tank and contaminate the oil so the bearing temperature is high and causes a trip or in the worst case, causing equipment damage. However, in reality, using an infusion system using human labor is still often constrained in terms of time efficiency, consistency and cost. Because every time this activity is carried out, the workers who do it are not always the same person and scheduled. Therefore the efficiency is still low. The purpose of this study was to determine the optimal method of handling the increase in water level in the turbine pit so that unit trips do not occur caused by the increase in the water level in the turbine pit. Finally, it is interesting to discuss and find a solution by relocating the handling of leaks by "using an automatic method with a motorized valve by installing a Motorized Valve on the Turbine Pit, so there are financial and non-financial benefits to be obtained. From the results of using the automatic method with a motorized valve, the results obtained are faster cycle times for handling leaks in the turbine pit so there is no stop unit due to leakage disturbances in the turbine pit.